Pogled na kariero in na podjetniške priložnosti - Boštjančič, Eva (Mednarodno inovativno poslovanje, 2012)
Technological development, economic changes, and changes in people's mindsets and needs are also influencing the development of careers and professions. Traditional society, which valued work, rules, and laws, is now disappearing and being replaced by ambitious, challenge-driven employees engaged in lifelong learning. Because of these changes, the current professions differ from those of the past as well as from emerging onesŽthat is, future professions. Professions that were once vital for preserving society are now disappearing due to automation of labor. Nonetheless, new professions are emerging that require trained staff able to perform them. The current development and emergence of new professions is primarily influenced by the retirement of the baby-boom generation, which will require even more trained medical staff, by developing information technology, and by the increasing focus on environmental changes and the related new environmental-protection professions. These findings have also been confirmed by a study conducted in Slovenia that examined Slovenians' views and opinions on career development and future professions.
Keywords: business organizations; occupations; podjetja; poklici